DMPC vesicle structure and dynamics in the presence of low amounts of the saponin aescin. Issue 14 (5th March 2018) - Sreij, Ramsia; Dargel, Carina; Geisler, Philippe; Hertle, Yvonne; Radulescu, Aurel; Pasini, Stefano; Perez, Javier; Moleiro, Lara H.; Hellweg, Thomas
Abstract : Vesicle shape and bilayer parameters are studied by small-angle X-ray (SAXS) and small-angle neutron (SANS) scattering in the presence of the saponin aescin. Bilayer dynamics is studied by neutron spin-echo (NSE) spectroscopy. Abstract : Vesicle shape and bilayer parameters are studied by small-angle X-ray (SAXS) and small-angle neutron (SANS) scattering in the presence of the saponin aescin. We confirm successful incorporation of aescin molecules by analysis of the radii of gyration R G and study furthermore the impact of aescin incorporation on bilayer thickness parameters from the neutron and X-ray perspective. Additionally, the bending elasticity ( κ ) of these 1, 2-dimyristoyl- sn-glycero -3-phosphocholine vesicle bilayers is studied in the presence of aescin. Neutron spin-echo spectroscopy (NSE) allows to detect subtle changes in the dynamics and κ of lipid membranes. Changes of κ are detectable at temperatures below and above the main phase transition temperature T m of the lipid. The impact of aescin is much more significant below T m . It has been found that below T m the addition of aescin to the vesicles decreases the value of κ and softens the bilayer. Above T m the value of κ increases with increasing aescin content and the bilayer becomes more rigid. Altogether, we demonstrate by analysis of the structure and dynamics of the vesicles that the impact of aescin strongly depends on the lipid state. Below T m the membrane becomes fluidized and softer, above T m solidified and stiffer compared to a DMPC membrane without additive at similar conditions.